Study on Effect of 3D Printing Parameters on Surface Roughness and Tensile Strength Using Analysis of Variance - Fadillah, Faqih; Suryanto, Heru; Suprayitno, Suprayitno (Universitas Negeri Malang, 2023)
Fused deposition modeling of 3D printing is the process of making workpieces or parts by adding filaments to each layer. Some indicators of a high-quality product of 3D printing are the precisions dimensions, the surface roughness, and tensile strength. This research aims to find the parameters most affecting surface roughness and tensile strength. The research design used an experimental method with input parameters: (1) print speed (15-35 mm/s), (2) print temperature (200-210°C), (3) layer height (0.1 – 0.3 mm), (4) infill line directions (0-90°), and dependent variables were surface roughness and tensile strength. The data distribution used the L9 orthogonal array, and the statistic analysis used ANOVA. Material uses nanographite-reinforced polylactic acid (PLA) filament. The results indicate that print parameters that significantly affect surface roughness are layer height and infill line directions. The best surface roughness on the layer height parameter is 0.1 mm, and the infill line directions parameter is 90°. Based on ANOVA analysis, print speed, print temperature, and layer height do not significantly affect tensile strength, but infill line directions significantly affect tensile strength. The best tensile strength on infill line directions is 90°. The best average tensile strength with nanographite-reinforced PLA filament is 38.56 N/mm2, with 35 m/s print speed, 205 °C print temperature, 0.1 mm layer height, and 90° infill line direction parameter. The best average surface roughness with nanographite-reinforced PLA filament is 0.66 µm, with 35 m/s print speed, 205 °C print temperature, 0.1 mm layer height, and 90° infill line direction parameter.